PENGARUH AKTIVITAS FISIK TERHADAP PERKEMBANGAN MOTOR SKILL PADA ANAK USIA 3-12 TAHUN: TINJAUAN PUSTAKA: - - Pradnyani, Tjokorda Istri Agung Rosanthi; Pramita, Indah; Tianing, Ni Wayan (Kinetic and Physiotherapy Comprehensive, 2024)
Background: Physical activity is vital in growth and development, maturation of motor and physiological functions, and cognitive abilities in the pediatric population. In children, sufficient physical activity is reported to help develop motor skills. This is because to have a good quality of movement, abilities obtained through habits in physical activity are needed. This study aimed to determine the effect of physical activity on the development of motor skills in children aged 3-12 years. Methods: The type of research was a literature review based on the review process of research articles that discuss the effect of physical activity on the development of motor skills in children aged 3-12 years. The search for articles was done from the Google Scholar and PubMed databases. Results: Based on the five selected journals in this literature review, significant positive results were obtained between physical activity and the development of motor skills in children aged 3-12 years old. The specifications of the motor skills that develop in children vary depending on the form, type, and settings of the physical activity. Conclusion: Physical activity seemed to affect the development of children's motor skills. The development of motor skills in children occurs gradually, along with physical development and stimulation of activities that spur better skills.